2013
DOI: 10.5130/cjlg.v0i13/14.3722
|View full text |Cite
|
Sign up to set email alerts
|

Decentralisation and Development: Can Uganda now pass the test of being a role model?

Abstract: Uganda's Government of the National Resistance Movement (NRM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…From the overall outcomes, the study indicated that policy formulation was generally modest in the Hoima district despite the setbacks faced in the phase of policy decision. This view was equally held by Ssonko (2013) in his study on the ability of Uganda to pass a role model test. During one of the interviews, the study participants stressed:…”
Section: Policy Decisionsmentioning
confidence: 89%
“…From the overall outcomes, the study indicated that policy formulation was generally modest in the Hoima district despite the setbacks faced in the phase of policy decision. This view was equally held by Ssonko (2013) in his study on the ability of Uganda to pass a role model test. During one of the interviews, the study participants stressed:…”
Section: Policy Decisionsmentioning
confidence: 89%
“…They are members of an elected body that makes decisions on behalf of a district local government through a formal meeting process. Councillors play a vital role in meeting the needs of local communities (Ssonko, 2019). They serve their communities by listening to people in the local area and then representing those views on council.…”
Section: The District Councilsmentioning
confidence: 99%
“…26 which are actually above 3.0, bears an indication that social factors do influence the performance of district councilors in their constituencies. No wonder literatures such as bySsonko (2019); and Kersting and Kuhlmann (2018) have worked in favor of this finding because they maintain that councillors play a vital role in meeting the needs of local communities, and they also serve their communities by listening to people in the local area and then representing those views on council. In a related development, qualitative findings appear to suggest that gender as one of the social factors is significant in determining the performance of councilors in constituencies.…”
mentioning
confidence: 99%
“…Meyer and Venter (2014) indicated that the lack of human resource management systems which are not conducive to recruiting and retaining personnel means that the recruitment process is more often than not compromised. It is in this context that Ssonko (2013) recommended that performance management is a key tool for managers and employees to set targets, achieve results and incentivize good performance, and provide interventions such as mentoring and coaching to overcome poor performance.…”
Section: Incompetent Human Resourcesmentioning
confidence: 99%